2005
DOI: 10.2224/sbp.2005.33.2.149
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits and Coping Styles as Mediators in Risky Sexual Behavior: A Comparison of Male and Female Undergraduate Students

Abstract: The aim in this study was to examine the extent to which differences in risky sexual behavior (RSB) between males and females is mediated by their personality traits and coping styles. Participants were 180 first-year undergraduate students who were evaluated with the Tridimensional Personality Questionnaire (Cloninger, 1987); the Multidimensional Coping Inventory (Carver, Scheier, & Weintraub, 1989); and a Risky Sexual Behavior Questionnaire. Findings showed that while the majority of the males had engaged in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…Others (e.g., Jaccard & Wilson, 1991), while in agreement with the second point, emphasize the need to conceptualize personality more specifically in sexual terms. Examples of general, nonsexual traits that have been studied and found relevant to the prediction of risky sexual behavior (e.g., number of sexual partners, consistency in using condoms) are sensation seeking, impulsivity, and harm avoidance (Bancroft et al, 2003(Bancroft et al, , 2004Gil, 2005;Hoyle et al, 2000;Lejueza, Bornovalovaa, Daughtersa, & Curtin, 2005), Examples of sexuality-related traits that have been found to be associated with risky sexual behavior are erotophilia (e.g., Fisher & Fisher, 1999) and the propensity for sexual inhibition (Bancroft et al, 2003(Bancroft et al, , 2004, as measured by the Sociosexual Orientation Survey (SOS) and the Sexual Inhibition/Sexual Excitation scales (SIS/SES), respectively. Interestingly, both measures have been found to be predictive of sexual responses in the laboratory (e.g., Janssen, Vorst, Finn, & Bancroft, 2002b;Janssen & Bancroft, 2007;Fisher, Byrne, White, & Kelley, 1988), which further supports the relevance of considering not just the role of (general and sexual) personality factors in risky sexual behavior, but also their possible psychophysiological correlates.…”
Section: Introductionmentioning
confidence: 99%
“…Others (e.g., Jaccard & Wilson, 1991), while in agreement with the second point, emphasize the need to conceptualize personality more specifically in sexual terms. Examples of general, nonsexual traits that have been studied and found relevant to the prediction of risky sexual behavior (e.g., number of sexual partners, consistency in using condoms) are sensation seeking, impulsivity, and harm avoidance (Bancroft et al, 2003(Bancroft et al, , 2004Gil, 2005;Hoyle et al, 2000;Lejueza, Bornovalovaa, Daughtersa, & Curtin, 2005), Examples of sexuality-related traits that have been found to be associated with risky sexual behavior are erotophilia (e.g., Fisher & Fisher, 1999) and the propensity for sexual inhibition (Bancroft et al, 2003(Bancroft et al, , 2004, as measured by the Sociosexual Orientation Survey (SOS) and the Sexual Inhibition/Sexual Excitation scales (SIS/SES), respectively. Interestingly, both measures have been found to be predictive of sexual responses in the laboratory (e.g., Janssen, Vorst, Finn, & Bancroft, 2002b;Janssen & Bancroft, 2007;Fisher, Byrne, White, & Kelley, 1988), which further supports the relevance of considering not just the role of (general and sexual) personality factors in risky sexual behavior, but also their possible psychophysiological correlates.…”
Section: Introductionmentioning
confidence: 99%
“…Temperament also did not predict actual sexual risk behaviors as well. While other studies have found that various constructs of temperament are predictive or associated with risk behaviors [ 21 , 23 , 25 , 26 ], none have examined all three constructs together that make up arousal, affect, and attention in one study; nor, has it been looked at with the interaction of context. Thus, in this sample temperament as a whole is not a factor in risky sexual intentions or behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Sensation seeking [ 21 23 ] and negative mood [ 23 , 24 ] are related to higher sexual risk intentions (i.e., choosing risky partners, intentions not to use condoms). Novelty-seeking, harm-avoidance, reward-dependence, and avoidant coping styles are related to actual behaviors of unprotected sex [ 25 ]. Gulletteand Lyons studied sexual sensation seeking and compulsivity in relation to HIV risk behaviors and found that although men scored higher than women on sexual sensation seeking, there were no gender differences in regards to sexual risk behaviors [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies indicated that gender plays a role in the method of coping used by adolescents. Researchers (Lengua and Stormshak, 2000;Gil, 2005) confirm that females prefer using social support, emotion-focused, and avoidant coping strategies relative to males. Males, on the other hand, seem to prefer using other activities to cope.…”
Section: Coping and Adolescentsmentioning
confidence: 99%